2020
DOI: 10.3390/molecules25225312
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Methylmalonic Aciduria by NMR Urinomics

Abstract: The paper reports on monitoring methylmalonic aciduria (MMA)-specific and non-specific metabolites via NMR urinomics. Five patients have been monitored over periods of time; things involved were diet, medication and occasional episodes of failing to comply with prescribed diets. An extended dataset of targeted metabolites is presented, and correlations with the type of MMA are underlined. A survey of previous NMR studies on MMA is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 70 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…As it concerns the NMR methodology in terms of field strength, 400 MHz (9.4 Tesla) magnets have been employed in most of the studies related to the reviewed pathologies [33,[41][42][43][44][45][46][47][49][50][51]54,55,58,71,73], and the results are suitable for the medical diagnosis of these pathologies. One 90 MHz (2.1 Tesla) study was reported [69].…”
Section: Nmr Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…As it concerns the NMR methodology in terms of field strength, 400 MHz (9.4 Tesla) magnets have been employed in most of the studies related to the reviewed pathologies [33,[41][42][43][44][45][46][47][49][50][51]54,55,58,71,73], and the results are suitable for the medical diagnosis of these pathologies. One 90 MHz (2.1 Tesla) study was reported [69].…”
Section: Nmr Methodologymentioning
confidence: 99%
“…Nicolescu et al [58] have monitored, by 1 H NMR at 600 MHz (14.1 Tesla), five MMA patients for several months at up to 9-year intervals. A comprehensive set of metabolites have been monitored in their urine.…”
Section: Non-localized Ex Vivo Nuclear Magnetic Resonance Spectroscop...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to targeted analysis for the diagnosis or confirmation of IEM, 1 H NMR metabolomic studies are also useful for monitoring the treatment of patients with IEM. Methylmalonic aciduria (OMIM 251000) is a good example that demonstrates how metabolic status can be evaluated, 40 because very different classes of substances can be quantified in one analysis, such as in this case orotic acid, methylmalonic acid, carnitine, glycine, and propionylcarnitine, which are related to the metabolic status of the patient and the severity of the enzyme defect methylmalonyl CoA mutase (OMIM 251000). In this respect other organic acidemias under treatment can also be monitored, such as propionic acidemia, isovaleric acidemia, and others (F.T., personal experiences).…”
Section: General Aspects Of Nmr Analysis In Biological Fluidsmentioning
confidence: 99%
“…Multivariate analysis of NMR spectra from various examples of aged meats allows the method, degree, and doneness of the aging process to be effectively differentiated and the key discriminatory metabolites to be identified. Special attention is given to the investigation of methylmalonic aciduria (MMA) by Nicolescu et al [ 5 ]. They report on monitoring MMA-specific and non-specific metabolites via NMR-based metabolomics and present an extended dataset of targeted metabolites.…”
mentioning
confidence: 99%